Identification, characterization, and developmental regulation of embryonic benzodiazepine binding sites - Borden, LA (J Neurosci, 1987)
We report the identification and characterization of 2 classes of benzodiazepine binding sites in the embryonic chick CNS. Binding was examined by competition and saturation binding experiments, using as radioligands 3H-flunitrazepam, a classical benzodiazepine anxiolytic, and 3H-Ro5–4864, a convulsant benzodiazepine. The results demonstrate that high-affinity (KD = 2.3 nM) 3H-flunitrazepam binding sites (site- A) are present by embryonic day 5 (Hamburger and Hamilton stage 27) and increase throughout development (Bmax = 0.3 and 1.3 pmol/mg protein in 7 and 20 d brain membranes, respectively). When 7 or 20 d brain membranes are photoaffinity-labeled with 3H-flunitrazepam and ultraviolet light, the radioactivity migrates as 2 bands on SDS-PAGE, consistent with Mrs of 48,000 and 51,000. GABA potentiates 3H- flunitrazepam binding at both 7 and 20 d of development, indicating that site-A is coupled to receptors for GABA early in development. Importantly, we have also identified a novel site (site-B) that binds classical benzodiazepine agonists with low affinity (micromolar) but displays high affinity for Ro5–4864 (KD = 41 nM). Site-B displays characteristics expected for a functional receptor, including stereospecificity and sensitivity to inactivation by heat and protease treatment. Saturation binding studies employing 3H-Ro5–4864 indicate that the levels of site-B are similar in 7 and 20 d brain (ca. 2.5 pmol/mg protein). The function of site-B is not known, but its preponderance in 7 d brain, relative to site-A, suggests that it might be important during early embryonic development.